The language of architecture 26 principles every architect should know - Simitch, Andrea; Warke, Val K. (Rockport Publishers, 2014)
"Learning a new discipline is similar to learning a new language; in order to master the foundation of architecture, you must first master the basic building blocks of its language - the definitions, function, and usage. Language of Architecture provides students and professional architects with the basic elements of architectural design, divided into twenty-six easy-to-comprehend chapters. This visual reference includes an introductory, historical view of the elements, as wells as an overview of how these elements can and have been used across multiple design disciplines. Whether you're new to the field or have been an architect for years, you'll want to flip through the pages of this book throughout your career and use it as the go-to-reference for inspiration, ideas, and reminders of how a strong knowledge of the basics allows for meaningful, memorable, and beautiful fashions that extend beyond trends. This comprehensive learning tool is the one book you'll want as a staple in your library." --Provided by publisher.